Population genomics of the invasive blackberry (Rubus niveus) in the Galapagos Islands - Carolina E. Armijos; José Cerca; Pablo Alarcón-Bolaños; Maria de Lourdes Torres (Global Ecology and Conservation, 2025)
Invasive species pose a major threat to biodiversity, especially in island ecosystems, and their control demands a substantial financial investment. R. niveus has emerged as a major threat to the biodiversity of these islands by displacing native and endemic species, and eradication efforts have failed so far. In this study, we use population genomics to study the genetics and possible introduction routes of the invasive alien plant Rubus niveus Thunb. in the Galapagos Islands. We used single digestion RAD-seq (sdRAD-seq) to generate a dataset comprising thousands of single-nucleotide polymorphisms (SNPs). Our findings reveal that R. niveus populations in the Galapagos and mainland Ecuador exhibit low levels of genetic diversity, and a certain degree of genetic differentiation between populations on the Galapagos and those on mainland Ecuador. Notably, we find that at least two distinct introductions of this plant species to the Galapagos might have occurred from the North/Center of mainland Ecuador, resulting in a rapid range expansion from its initial arrival. Despite its limited genetic diversity, R. niveus has succeeded in expanding throughout the Galapagos. Our results show that the population genetics of invasive alien species are critical to inform and further devise effective management strategies to mitigate biodiversity losses over time.